Delayed upper tract drainage on voiding cystourethrogram may not be associated with increased risk of urinary tract infection in children with vesicoureteral reflux. Issue 5 (October 2016) - Garcia-Roig, Michael; Arlen, Angela M.; Huang, Jonathan H.; Filimon, Eleonora; Leong, Traci; Kirsch, Andrew J.
Summary: Introduction: Urinary stasis in the setting of obstruction provides an opportunistic environment for bacterial multiplication and is a well-established risk factor for UTI. Vesicoureteral reflux (VUR) with delayed upper tract drainage (UTD) on VCUG has been reported to correlate with increased UTI risk. We sought to determine whether delayed UTD can be reliably classified, and whether it correlates with UTI incidence, VCUG, or endoscopic findings. Methods: Children undergoing endoscopic surgery for primary VUR (2009–2012) were identified. VUR grade, timing, and laterality were abstracted. Demographics, hydrodistention (HD) grade, reported febrile and culture-proven UTI were assessed. UTD on VCUG was graded on post-void images as 1 = partial/complete UTD or 2 = no/increased UTD. Inter-observer agreement was calculated. Patients were excluded for incomplete imaging or inability to void during VCUG. Results: The cohort included 128 patients (10M, 118F), mean age 4.1 ± 2.1 years. Mean age at diagnosis was 2.8 ± 2.8 years. Mean maximum VUR grade was 3 ± 0.9: 1 (7.8%), 2 (20.3%), 3 (43%), 4 (25.8%), 5 (3.1%). UTD occurred in 45 (35%), and no drainage in 83 (65%) patients. Agreement coefficient between graders was 0.596 ( p < 0.0001). Cultures were available in 100 patients (70 positive). Patients experienced a mean of 2 ± 1.2 parent-reported fUTIs and 1.2 ± 1.2 culture-proven UTIs from birth to surgery. UTI rate did not differ by UTD status for parent or culture-proven UTI (Table). On multivariate analysis, no patient characteristic was a significant predictor of UTI based on drainage status. Children diagnosed with VUR before 1 year of age had a higher verified UTI rate ( p < 0.001). However, drainage was not a significant predictor of UTI rate and when testing the interaction of drainage and age. Conclusion: We sought to determine whether UTD was an accurate predictor of UTI risk to maximize available prognostic information from a single VCUG. Delayed UTD was not a predictor of infection in our patients, nor was it associated with previously described UTI risk factors, such as VUR timing or grade, and voiding dysfunction. Limitations included the retrospective nature of the study in patients undergoing endoscopic VUR treatment, and possible inaccurate UTI reports from parents and pediatricians. UTD can be reliably scored using a binary system with high inter-observer correlation. Our data call into question the previous finding that children with poor UTD are at increased risk of recurrent UTI. Delayed UTD is also not associated with higher HD, or VUR grade compared with those with more prompt UTD. Table Urinary tract infection rate/year by parent reported and positive culture UTI versus upper tract drainage on voiding cystourethrogram according to binary drainage scoring system. Urinary tract infection vs. upper tract drainage p -value N Mean (SD) Median (mad) UTI rate/year by parent reported UTI Complete upper tract contrast drainage or less than filling 45 0.66 (0.53) 0.47 (0.28) 0.71 Unchanged upper tract contrast or more than filling 83 0.7 (0.5) 0.62 (0.33) UTI rate/year by positive culture Complete upper tract contrast drainage or less than filling 24 0.746 (0.657) 0.47 0.1664 Unchanged upper tract contrast or more than filling 49 0.538 (0.410) 0.441